2013
DOI: 10.1128/jvi.01023-13
|View full text |Cite
|
Sign up to set email alerts
|

Single Hemagglutinin Mutations That Alter both Antigenicity and Receptor Binding Avidity Influence Influenza Virus Antigenic Clustering

Abstract: The hemagglutination inhibition (HAI) assay is the primary measurement used for identifying antigenically novel influenza virus strains. HAI assays measure the amount of reference sera required to prevent virus binding to red blood cells. Receptor binding avidities of viral strains are not usually taken into account when interpreting these assays. Here, we created antigenic maps of human H3N2 viruses that computationally account for variation in viral receptor binding avidities. These new antigenic maps differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 28 publications
7
85
0
Order By: Relevance
“…We completed HAI assays using antisera generated against A/Victoria/361/2011 (Influenza Reagent Resource, Atlanta, GA) and found that viruses with the P237L HA mutation had reduced HAI titers (Fig. 1C), which is consistent with previous studies demonstrating that viruses with higher avidity are difficult to inhibit in HAI assays (3,19,20). Using Sanger sequencing, we did not detect the P237L HA mutation in the original clinical material of isolate 6 (Table 2); however, we were able to detect low levels of this mutation in the original clinical isolate after sequencing individual clones following TA cloning (TOPO TA Cloning kit; Life Technologies, Carlsbad, CA) of PCR products (Fig.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…We completed HAI assays using antisera generated against A/Victoria/361/2011 (Influenza Reagent Resource, Atlanta, GA) and found that viruses with the P237L HA mutation had reduced HAI titers (Fig. 1C), which is consistent with previous studies demonstrating that viruses with higher avidity are difficult to inhibit in HAI assays (3,19,20). Using Sanger sequencing, we did not detect the P237L HA mutation in the original clinical material of isolate 6 (Table 2); however, we were able to detect low levels of this mutation in the original clinical isolate after sequencing individual clones following TA cloning (TOPO TA Cloning kit; Life Technologies, Carlsbad, CA) of PCR products (Fig.…”
supporting
confidence: 74%
“…The addition of oseltamivir directly into HAI assays may circumvent this problem (9). We have previously shown that HA mutations that alter receptor binding avidity can skew antigenic maps based on HAI assays (20), and , T329N Q49R, T144A, R158G, N161S, F209S, N294K P237L 2 Low K258E, T329N T144A, R158G, N160S, N161S, N294K 3 Low K128R, V143M, K258E, T329N Q49R, N161S, N294K 4 Low P79S, G93D, E221D, K258E, T329N Q49R, N161S, N294K 10 Low K258E, T329N Q49R, (20,21). Future studies should focus on alternative cell-derived systems for propagating primary influenza isolates, such as MDCK cells engineered to express different types of sialic acid receptors (12,22).…”
mentioning
confidence: 99%
“…Antigenic changes can come at a cost of fitness, sometimes due to lower avidity to sialic acids, and substitutions outside the antigenic motif may be compensatory mutations or simply hitchhiker mutations (43,44,54,55). We selected one OH/04 mutant with large antigenic changes to assess in vivo other virus properties and found that its replication in the upper and lower respiratory tract in directly inoculated pigs was comparable to that of wt OH/04 but caused significantly lower levels of lung lesions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Positions 145, 155, 156, 158, 159, and 189 included in the putative antigenic motif are located adjacent to the RBS, and others have reported that modifications of HA antigenicity can cause changes in sialic acid binding properties (42)(43)(44)(45)(46). Even though the substitutions introduced in the OH/04 mutants match amino acids known to exist in circulating strains, additional mutations in the HA, as well as epistatic mutations in the NA, can arise to compensate for loss of receptor avidity and/or affinity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data suggest that many, if not most, HA mutations simultaneously alter both antigenicity and receptor binding avidity (13)(14)(15)(16)(17). Using a mouse model, we recently demonstrated that viruses with increased receptor binding avidity are favored in vaccinated animals, while viruses with decreased receptor binding avidity are favored in naive animals (13).…”
mentioning
confidence: 99%